DEVELOPMENT OF VIDEO LEARNING MEDIA FOR CASUAL FASHION DESIGN CLASS X FASHION MANAGEMENT AT SMK NEGERI 1 AMPEK ANGKEK - Kiki Khairani; Agusti Efi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This study aims to develop video learning materials for the Fashion Design subject in Fashion Design class X at SMK Negeri 1 Ampek Angkek. The problems identified include conventional teaching methods, low student motivation and creativity, and many students who have not achieved the Minimum Completion Criteria (KKM). Video learning materials have been developed to visualize the concept and steps of designing casual clothing in a more effective and interesting way. This study uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The results of the study indicate that the developed video learning media is useful and practical for use in the learning process, and is able to improve students' understanding and creativity in designing clothing.